2022
DOI: 10.1186/s12913-022-07696-x
|View full text |Cite
|
Sign up to set email alerts
|

System-level policies on appropriate opioid use, a multi-stakeholder consensus

Abstract: Background This consensus statement was developed because there are concerns about the appropriate use of opioids for acute pain management, with opposing views in the literature. Consensus statement on policies for system-level interventions may help inform organisations such as management structures, government agencies and funding bodies. Methods We conducted a multi-stakeholder survey using a modified Delphi methodology focusing on policies, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…The Delphi method is a well-known process used for obtaining group consensus in healthcare, as it encourages decision making and new ideas to be formed by whole group feedback [ 15 , 16 ]. The method involves several rounds of anonymous questionnaires, where after each round structured feedback and aggregated responses from previous rounds are presented to panellists ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Delphi method is a well-known process used for obtaining group consensus in healthcare, as it encourages decision making and new ideas to be formed by whole group feedback [ 15 , 16 ]. The method involves several rounds of anonymous questionnaires, where after each round structured feedback and aggregated responses from previous rounds are presented to panellists ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Over 50% of patients complain of moderate to severe pain despite medical treatment [30]. Reasons of mismanagement of cancer pain can be related to physicians (undertreatment due to fear of side effects, no patient education, underestimation of pain, poor communication between patients and doctors, or no application of pain control guidelines) and to patients (scarce adherence to treatment, fear of side effects, lack of communication between patients and doctors, or pain considered as "normal") [23,27,31,32].…”
Section: Treatment Of Cancer Painmentioning
confidence: 99%
“…Liberal prescribing of opioids for postoperative pain relief increases the risk of persistent postoperative opioid use and adverse outcomes, which has reached epidemic proportions in certain countries, especially in the USA (Jalal et al, 2018). These adverse outcomes include dependence, addiction, opioid use disorders, opioid-induced ventilatory impairment and overdose-related deaths (Forget et al, 2022). A study by Gomes et al (2018) assessed the burden of opioid-related deaths in the USA and found that the percentage of all deaths attributable to opioids increased by an alarming 292% (from 0.4-1.5%) between 2001 and 2016.…”
Section: Introductionmentioning
confidence: 99%